2008
DOI: 10.1128/aac.00955-07
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Piperaquine after Two Different Treatment Regimens with Dihydroartemisinin-Piperaquine in Patients with Plasmodium falciparum Malaria in Thailand

Abstract: The population pharmacokinetics of piperaquine in adults and children with uncomplicated Plasmodium falciparum malaria treated with two different dosage regimens of dihydroartemisinin-piperaquine were characterized. Piperaquine pharmacokinetics in 98 Burmese and Karen patients aged 3 to 55 years were described by a two-compartment disposition model with first-order absorption and interindividual random variability on all parameters and were similar with the three-and four-dose regimens. Children had a lower bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
127
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 30 publications
16
127
1
Order By: Relevance
“…Most previous studies have used a two-compartment model (28,31,44). One study in healthy adults found that, although a three-compartment model represented the postadministration profile better, there were insufficient data to support its use over a two-compartment model (38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies have used a two-compartment model (28,31,44). One study in healthy adults found that, although a three-compartment model represented the postadministration profile better, there were insufficient data to support its use over a two-compartment model (38).…”
Section: Discussionmentioning
confidence: 99%
“…The current manufacturer's recommendation is for Artequick to be given as a 2-day regimen, which contrasts with the 3 days recommended for all ACTs by the WHO (48). Although the tolerability, safety, efficacy, and pharmacokinetics (PK) properties of DHA-PQ tetraphosphate have been widely investigated in children and adults (27,28,36,44,49), there are limited data relating to the efficacy and tolerability of ART-PQ base (37,46) and no studies of the pharmacokinetics of this novel combination in malaria-infected patients. Concerns have been raised regarding possible underdosing in children for a number of antimalarial drugs (8,33), including PQ (27,36,49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to prevent drug resistance and early parasite recrudescence associated with the short-acting artemisinin drugs, ACT partner drugs should be long-acting schizonticides with half-lives (t 1/2 s) exceeding 4 days, or two asexual parasite life cycles (10,21). Recent pharmacokinetic studies have demonstrated that PQ has biphasic elimination and a long terminal t 1/2 of 12 to 28 days in humans (10,15,31,32).…”
mentioning
confidence: 99%
“…In order to prevent drug resistance and early parasite recrudescence associated with the short-acting artemisinin drugs, ACT partner drugs should be long-acting schizonticides with half-lives (t 1/2 s) exceeding 4 days, or two asexual parasite life cycles (10,21). Recent pharmacokinetic studies have demonstrated that PQ has biphasic elimination and a long terminal t 1/2 of 12 to 28 days in humans (10,15,31,32).Several clinical trials of the PQ-dihydroartemisinin combination have shown that it has a high degree of efficacy and good tolerability for the treatment of Plasmodium falciparum infections (1,2,5,7,11,12,17). While this combination is now considered the first-line antimalarial treatment in some Southeast Asian countries, the long t 1/2 of PQ raises concerns about adverse effects and drug resistance (6,10,20,22).…”
mentioning
confidence: 99%